The Influence of Internal Quality Assurance System on Quality Improvement of Accreditation in State Islamic Religious Universities Using The Technology Acceptance Model (TAM) - Hidayat, Wahyu; Ardyanti, Yefi; Wulan, Elis Ratna (JURNAL AL-TANZIM, 2023)
This study aims to analyze the effect of the internal quality assurance system on improving the accreditation quality of State Islamic Higher Education by using the Technology Acceptance Model (TAM). The research method used is quantitative. The research is an explanatory survey explaining the influence of the variables contained in the SPMI Information System in Higher Education. The research results show that; 1) There is a positive and significant effect of 62.4% both partially and simultaneously on all TAM variables on the use of the SPMI system; 2) There is a positive and significant effect of 53.5% both partially and simultaneously on all SPMI information system variables on improving the quality of accreditation. This research has implications for the importance of using other resources to improve the quality of education in tertiary institutions.